Consumer behavior : building marketing strategy - Hawkins, Del I.; Best, Roger J.; Mothersbaugh, David L. (Irwin/McGraw-Hill series in marketing, 2007)
Covers consumer behavior including the psychological, social, and managerial implications. This work features examples that are tied into global and technology consumer behavior issues and trends, a foundation in marketing strategy, integrated coverage of ethical/social issues, and outlines the consumer decision process